2017
DOI: 10.1111/jphp.12748
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aqueous extract and anthocyanins of calyces of Hibiscus sabdariffa (Malvaceae) in rats with adenine-induced chronic kidney disease

Abstract: The results obtained show that both H. sabdariffa and its anthocyanins could be considered as possible promising safe dietary agents that could be used to attenuate the progression of human CKD. This could have added significance as H. sabdariffa tea is widely consumed in many parts of Africa and Asia and is thus readily available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…However, using an adenine-induced CKD model in rats recently showed that administration of anthocyanins lessened the effects of adenine-induced CKD. 71 The underlying mechanism of the positive effect of anthocyanins in this rat model was suggested to be by acting as an antagonist to oxidative stress and by decreasing the inflammation response. Anthocyanins could therefore be a potential dietary agent to consider in the treatment of CKD.…”
Section: Targeting Mitochondrial Dysfunction In Ckdmentioning
confidence: 89%
See 1 more Smart Citation
“…However, using an adenine-induced CKD model in rats recently showed that administration of anthocyanins lessened the effects of adenine-induced CKD. 71 The underlying mechanism of the positive effect of anthocyanins in this rat model was suggested to be by acting as an antagonist to oxidative stress and by decreasing the inflammation response. Anthocyanins could therefore be a potential dietary agent to consider in the treatment of CKD.…”
Section: Targeting Mitochondrial Dysfunction In Ckdmentioning
confidence: 89%
“…Although anthocyanins seem to be electron acceptors in complex I‐mediated oxidation of NADH and provide cardioprotection, the effects of this polyphenol have not been tested in the context of CKD. However, using an adenine‐induced CKD model in rats recently showed that administration of anthocyanins lessened the effects of adenine‐induced CKD . The underlying mechanism of the positive effect of anthocyanins in this rat model was suggested to be by acting as an antagonist to oxidative stress and by decreasing the inflammation response.…”
Section: Nutritional Strategies Targeting Mitochondrial Dysfunction Imentioning
confidence: 97%
“…Notably, delphinidin also prevents muscle atrophy in mice (266) and lowers fasting glycaemia in prediabetic individuals (267). Moreover, dietary supplementation with anthocyanins isolated from roselle (Hibiscus sabdarrifa) attenuated progression of adenineinduced CKD in rats (268). Since a causal role for senescent cells in ageing-related bone loss has been demonstrated in mice (269) nutritional compounds with senolytic effects , such as quercetin and fisetin (270) -found in fruits, capers, vegetables and berries -may also contribute to the capacity of bears to maintain their bone mass (242).…”
Section: Major Differences Exist In Levels Of Serum Biomarkers Of Micmentioning
confidence: 99%
“…The pathophysiological basis of CKD and its complications include inflammation, oxidative stress and apoptosis, features that are always seen in human beings and animals with CKD [14-16]. There are also major mediators of the disease such as C-reactive protein, tumor necrosis factor and other cytokines, and several markers of nitrosative and oxidative stress, exerting similar effects in CKD models in rats [16-19].…”
Section: Introductionmentioning
confidence: 99%